Knowing about Genocide: Armenian suffering and epistemic struggles - Savelsberg, Joachim Josef (University of California Press, 2021)
Inhaltsverzeichnis: Preface : purpose, author, and acknowledgments -- Introduction : epistemic circle and history of the Armenian genocide -- Social interaction, self-reflection, and struggles over genocide knowledge -- Diaries and bearing witness in the humanitarian field -- Carriers, entrepreneurs and epistemic power : conceptual toolbox toward an understanding of genocide knowledge -- Sedimentation and mutations of Armenian knowledge about the genocide -- Sedimentation of Turkish knowledge about the genocide, and comparisons -- Affirming genocide knowledge through rituals -- Epistemic struggles in the political field : mobilization and legislation in France -- Epistem struggles in the legal field : speech rights, memory, and genocide : curricula before an American court (with Brooke B. Chambers) -- Denialism in an age of human rights hegemony -- Conclusions : closing the epistemic circle and future struggles.